Influences on science education: the use of Supplemental Instruction on academic success in introductory sciences courses at a two year community college - Williams, T. S., author; Gloeckner, Gene, advisor; Anderson, Sharon, committee member; Balgopal, Meena, committee member; Klopfenstein, Ken, committee member (Colorado State University. Libraries, 2014)
This dissertation uses a mixed method design model to investigate the influences of Supplemental Instruction (SI) on student final grade outcomes in introductory science courses at the community college level. The literature states that student comprehension in the field of science is critical; however, educators are discovering that certain student demographics are falling behind in science comprehension. The research focuses on the issue of disparity among different demographics and analyzes whether the introduction of the academic intervention technique, Supplemental Instruction (SI), increases the academic success of students in introductory community college biology and chemistry courses. A series of Two Way ANOVA analyses revealed that the use of SI had a positive effect (i.e., increased final grade outcomes) on community college student demographics; however, in some sections, a negative final grade outcome was found. In this study, data indicate that SI supported biology classes had a greater effect (or positive direction) on Black Non-Hispanic overall final grades. However, White Non-Hispanic students enrolled in SI supported introductory biology courses showed a slight decrease (or negative direction) in marginal means (d = -0.180). Hispanic students enrolled in SI supported courses showed a very slight increase (or positive direction) in final grade outcomes (d = 0.11). Another analysis outlined in this study showed the impact of SI on student grades in introductory science courses and first-generation student status. The analysis indicates a positive direction between the use of SI in an introductory science course on overall student final grades and student first-generation status. The data indicate that with the use of SI in an introductory science course, student final grades in the first generation student population showed an effect size of d = 0.1897. These data indicate that SI supported science courses had a positive effect on First Generation student overall final grades. The research examined the impact of SI on the principle SI Student Leaders (SISL) and found that student participation in the program had positive influences on SISL discipline comprehension, engagement, overall course satisfaction.